Seroprevalence and risk factors of schmallenberg virus (Sbv) infection among selected small ruminants farms in Negeri Sembilan, Malaysia - Nur Iffah Husna Muhamad Sedek (2019)
Schmallenberg virus (SBV) is a virus recently discovered in Germany in the year 2012. SBV infection occurs prominently in cattle, followed by small ruminants such as sheep and goats. Numerous study on the virus has been conducted in European countries such as Germany, Netherlands, and France. In Malaysia, the degree of this infection is still unknown. Hence, this study was aimed to investigate the seroprevalence and risk factors of SBV infection among small ruminants in the state of Negeri Sembilan. Blood samples were randomly collected from three small ruminant farms in Negeri Sembilan. Parameters such as age, breed, gender and reproductive status were recorded and farmers were interviewed regarding the farm and animal management. Sera obtained from centrifugation of blood samples are subjected to serology testing by using ID-VET Schmallenberg virus Competition Multi-species ELISA kit. Data analysis was done by using JMP Statistical Software with the P-value calculated using Pearson Chi-Square. In this study, the result revealed that 59 out of 182 samples were positive towards SBV infection with a seroprevalence rate of 32.42% and the significant risk factors being species, reproductive status, management, ownership and breed. Goats (40 %) showed higher seroprevalence rate compared to sheep (20.83% in this study. Pregnant animals had the highest seroprevalence rate (78.95%) followed by mature animals (34.18%), lactating animals (30%) and lastly the immature animals group (11.36%). Furthermore, semi-intensive management (55.10%) showed the highest seroprevalence rate compared to extensive management (35.14%) and intensive management (10.17%). Private small ruminant • farms (43.09%) had higher seroprevalence rate than government farms (10.17%). For goats, Boer (50%) had showed higher seroprevalence rate compared to local breeds (35.14%). In sheep, mixed-breed sheep (69.23%) had higher seroprevalence rate than pure White Dorpers (10.17%). As conclusion, detection of positive seroprevalence towards SBV infection in this study showed a new breakthrough that this SBV disease among small ruminant in Malaysia is a newly reported disease and an emerging viral disease in ruminants of Malaysia. Therefore, it is suggested to conduct overall study in all states on Malaysia with a larger sample size involving large and small ruminants to know the true prevalence and endemicity of SBV infection among ruminants in Malaysia.